Developing conveyor trainer kit for programmable logic controllers in practical learning - Sukir Sukir; Soenarto Soenarto; Soeharto Soeharto (Jurnal Pendidikan Vokasi, 2017)
The research aims: (1) to produce conveyor trainer kit equipped with a monitoring system along with its work performance, (2) to know the appropriateness and effectiveness of the use of conveyor trainer kit and module of PLC practical learning. This study is a development research using ADDIE model based on Branch, RB. The steps of this study are: analysis, designing, developing, implementation, and evaluation. Data collection is conducted through observation, survey, and test by using the instruments: observation sheets, questionnaire, and examination. The data are analyzed descriptively using nonparametric test of difference by Mann Whitney. The finding shows: (1) the product of conveyor trainer kit equipped with monitoring system has good work performance; (2) conveyor trainer kit and the module are very appropriate, and the implementation of conveyor trainer kit and module of PLC practical learning can improve student learning outcomes in cognitive, psychomotor, and affective aspects effectively.